2010
DOI: 10.1017/s1092852900000365
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine for the Treatment of Generalized Social Anxiety Disorder: A Preliminary Randomized Trial of Increased Dose to Optimize Response

Abstract: Objective: This is the first trial examining duloxetine for generalized social anxiety disorder (GSAD) and the effect of increased dose for those without early remission.Methods: Individuals (n=39) with GSAD received 6 weeks of open-label duloxetine 60 mg/day; those with a Liebowitz Social Anxiety Disorder Scale (LSAS) score >30 at week 6 were randomized in double-blind fashion to an additional 18 weeks of continued duloxetine 60 mg/day or to duloxetine 120 mg/day.Results: Duloxetine was associated with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…1 While pharmacotherapy and psychotherapy are common treatment strategies, 30 to 60% of patients do not achieve remission after treatment. 2-6 In one early naturalistic study of 164 patients with GAD predominantlytreated with pharmacotherapy,remission was as low as 15%. 7 Further, individuals with GAD may not seek care in psychiatric settings due to perceived stigma.…”
Section: Introductionmentioning
confidence: 99%
“…1 While pharmacotherapy and psychotherapy are common treatment strategies, 30 to 60% of patients do not achieve remission after treatment. 2-6 In one early naturalistic study of 164 patients with GAD predominantlytreated with pharmacotherapy,remission was as low as 15%. 7 Further, individuals with GAD may not seek care in psychiatric settings due to perceived stigma.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 278 studies were initially identified through the electronic search. First pass screening eliminated, leaving 30 studies (Stahl et al ., ; Koponen et al ., , ; Allgulander et al ., , ; Hartford et al ., , ; Russell et al ., , ; Davidson et al ., ; De Berardis et al ., ; Hoschl and Svestka, ; Norman and Olver, ; Pollack et al ., ; Rynn et al ., ; Trivedi et al ., ; Katzman, ; Kornstein et al ., ; Nicolini et al ., ; Simon et al ., , ; Pangallo et al ., ; Wu et al ., , ; Bodkin et al ., ; Piero and Locati, ; Sheehan et al ., ; Karaiskos et al ., ; Mavranezouli et al ., ; Alaka et al ., ) were considered potentially relevant for further inspection. After screening the full text, seven randomized controlled trials (RCTs) (Hartford et al ., ; Koponen et al ., ; Davidson et al ., ; Rynn et al ., ; Nicolini et al ., ; Wu et al ., ; Alaka et al ., ) ( n = 2,674) were available for meta‐analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, the treatment of GAD has involved a number of different classes of medications, including benzodiazepines, tricyclic antidepressants (TCAs), buspirone hydrochloride, selective serotonergic reuptake inhibitors (SSRIs) (Clark et al ., ; Vasile et al ., ), noradrenergic and specific serotonergic drug (Gutierrez et al ., ; Schutters et al ., ; Simon et al ., ; Reinhold et al ., ). SSRIs are generally better tolerated by the patients than TCAs and have similar efficacy (Anderson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Venlafaxine is the only serotonin-norepinephrine reuptake inhibitor (SNRI) studied in RCT in patients with social phobia, but improvements in social phobia symptom ratings have also been shown in an open-label trial of the SNRI, duloxetine 45. All five reported studies23,28,4648 have shown significantly greater response rates for venlafaxine compared with placebo (Figure 2, OR range for treatment response 1.89–3.78).…”
Section: Resultsmentioning
confidence: 99%